2023
DOI: 10.3389/fneur.2023.1120286
|View full text |Cite
|
Sign up to set email alerts
|

Laser interstitial thermal therapy (LITT) for pediatric patients affected by intracranial tumors

Abstract: IntroductionThe surgical treatment of brain tumors has evolved over time, offering different strategies tailored to patients and their specific lesions. Among these strategies, Laser Interstitial Thermal Therapy (LITT) is one of the most recent advances in pediatric neurooncological surgery, and its results and evolution are still under assessment.MethodsWe retrospectively analyzed data from six pediatric patients with deep-seated brain tumors treated with LITT at a single center between November 2019 and June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Moreover, the comparatively smaller sample sizes and varied patient demographics in different studies could have impacted the observed heterogeneity and effect sizes. These limitations have been reported in multiple studies, emphasizing the critical need for more extensive, well‐designed studies incorporating control groups to provide more conclusive insights into the intricate relationship between LITT and wound complications in brain tumour patients 32–35 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the comparatively smaller sample sizes and varied patient demographics in different studies could have impacted the observed heterogeneity and effect sizes. These limitations have been reported in multiple studies, emphasizing the critical need for more extensive, well‐designed studies incorporating control groups to provide more conclusive insights into the intricate relationship between LITT and wound complications in brain tumour patients 32–35 …”
Section: Discussionmentioning
confidence: 99%
“…Laser interstitial thermal therapy (LITT) is a neurosurgical technique that is becoming increasingly popular in the pediatric population 2,3 . PLGGs commonly involve deep and eloquent regions; such as thalamic or thalamo-peduncular, periventricular, and other subcortical locations.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current literature on LITT for brain tumors focuses on high-grade gliomas and brain metastases in adults, as well as for radiation necrosis following their treatment. The evidence for the use of LITT in low-grade gliomas (LGGs), especially in the pediatric population, is still evolving 3 . In pediatrics, LITT has been used to treat a variety of pathologies, including hypothalamic hamartomas, pilocytic astrocytomas, and subependymal giant cell astrocytomas, among others 2 .…”
Section: Introductionmentioning
confidence: 99%
“… 22–26 The low-grade characteristics of our patient’s tumor also portended a high probability of long-term success, given other reports in the literature suggesting optimal efficacy of LITT for children with low-grade rather than high-grade gliomas. 29 Although not extensively studied in superficial tumors, LITT is generally reserved for tumors with deep-seated origins, including thalamic, peduncular, and periventricular locations, offering substantial reductions in morbidity and mortality risks over open surgery. 29 Thus, the low-grade tumor characteristics and periventricular location of our patient’s tumor favored intervention with LITT over craniotomy and microdissection.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Although not extensively studied in superficial tumors, LITT is generally reserved for tumors with deep-seated origins, including thalamic, peduncular, and periventricular locations, offering substantial reductions in morbidity and mortality risks over open surgery. 29 Thus, the low-grade tumor characteristics and periventricular location of our patient’s tumor favored intervention with LITT over craniotomy and microdissection.…”
Section: Discussionmentioning
confidence: 99%